(untitled) (Ameghiniana, 2013)
The palynogical study of a complete section of Loreto Formation in its type locality, near Punta Arenas, Chile, is here presented. In the first part, a brief exposition of the geographical and the geological knowledge of the area is included, followed by a detailed description of the stratigraphical column there outcropping. The second part deals with the study of the palynomorphs, recording the presence of at least 40 of them, most here described; 10 belong to palaeomicroplanktonic elements while the rest include spores and pollen grains of continental origino The palynomorphs with some chronological value seem to prove an age ranging from Upper Eocene to Lower-Middle Oligocene. On the other hand, some taxa can be of use for regional stratigraphy, such as Deflandrea granulata, Hystrichospbaera sp., Tricolporites spp. 1 and 2. A comparison of the palynomorphs from Loreto and the subjacent Leña Dura Formation, indicates a continuity of the continental components, but there are variations as far as the microplankton is concerned. Some forms which have ecological importance were found; the analysis of their maxima and minima in frequency diagrams, in some representative levels as E and 1 suggest conditions of palynologically dominant Fagaceae woods, with a slightly wet climate and a rain fall approaching 1000-1700mm per year with an average temperature near 12° C; while in other levels, as F and G, the conditions indicate the dominance of Gymnospermous woods, which are characteristic of wet climate, with an average rain fall of about 2300-2500 mm and a ternperature of about 12° C. East-West floristic profiles are also included for these levels. The composite diagram Fagaceae: Gymnosperrnae, indicates a remarkable antagonismo This could be explained according to the ectotrophic and anectotrophic woods theory, in a similar way as it is used for the same groups now living in the southern forests of Chile. A comparison among species of the palaeoflora described by Dusén for the Río de las Minas Ríver, and the palynomorphs here described, would indicate a possible affinity of Nothofagidites cincta, N. d. N. waipawaensis and/or N. d. N. cranwellae, and Araucariacites sp., with three species described by the named author, based on leaf morphology.